UNA NUEVA ARAUCARIACEAE CRETACICA DE PATAGONIA, ARGENTINA (Ameghiniana, 2013)
Nothopehuen brevis is a new Conifer genus, from the lower cretaceous strata of the Baqueró Forrnation (Santa Cruz Province), that belongs to the family Araucariaceae.Nothopehuen is based on male cones that contain grains of the Araucariacites type, organically attached to branches with small leaves of the Brachyphyllum type. The cuticle of leaves, sporophylls and the pollen grains were studied with light microscopy as well as with scanning and transmission electronic microscopy. Comparisons are made with fossil and extant taxa of the family. Nothopehuen confirms that the Araucariaceae were important components, together with other conifers of the early Cretaceous flora that lived in Patagonia.